Circadian rhythm of metabolic rates in the saliva of patients with arterial hypertension against the background of type 2 diabetes mellitus - A. I. Gozhenko; Yu. M. Hryshko; T. V. Gorbach (Kazimierz Wielki University, 2019)
According to our hypothesis, one of the mechanisms in the development and progression of cardiovascular diseases may be metabolic changes that are inadequate with the functional responses of adaptation, indicating the disruption of the functional and metabolic continuum (FMC). We suggested to study the daily rate of change in metabolism and hormonal regulation (morning vs. evening) in the saliva to diagnose the FMC disorders. In order to detect the FMC changes in patients with diabetes mellitus (DM2) complicated by arterial hypertension (AH), we studied the parameters of FMC and endocrine regulation in the saliva in the morning and in the evening as compared to patients with diabetes mellitus. Previously, we have shown that in compensated DM2, there are changes in the energy metabolism, induced by hormonal regulation. These changes can be controlled with daily saliva monitoring. The study of the daily rhythm of in the saliva parameters makes it possible to conclude that in DM2, and especially in its progress, as evidenced by the accession of hypertension, there are disorders of FMC. One of its consequences is the development of oxidative stress, which is considered as one of the leading secondary mechanisms in the pathogenesis of DM2.